2013
DOI: 10.1353/lan.2013.0068
|View full text |Cite
|
Sign up to set email alerts
|

Error and expectation in language learning: The curious absence of mouses in adult speech

Abstract: As children learn their mother tongues, they make systematic errors. For example, English-speaking children regularly say mouses rather than mice . Because children’s errors are not explicitly corrected, it has been argued that children could never learn to make the transition to adult language based on the evidence available to them, and thus that learning even simple aspects of grammar is logically impossible without recourse to innate, language-specific constraints. Here, we examine the role children’s expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
238
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(252 citation statements)
references
References 152 publications
12
238
0
2
Order By: Relevance
“…Ramscar, Dye, and McCauley (2013) proposed a much simpler model, based on ideas from learning theory, that attempts to explain how children master morphology (rather than syntax). In particular, the model attempts to learn which of a scene's semantic features are the best predictors of its appropriate phonological label (e.g.…”
Section: Prediction-based Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…Ramscar, Dye, and McCauley (2013) proposed a much simpler model, based on ideas from learning theory, that attempts to explain how children master morphology (rather than syntax). In particular, the model attempts to learn which of a scene's semantic features are the best predictors of its appropriate phonological label (e.g.…”
Section: Prediction-based Learningmentioning
confidence: 99%
“…1 The successful completion of this enterprise will be greatly helped by the explicit computational models that have been developed in this area (e.g. Chang et al, 2006;Ramscar et al, 2013). These can generate accurate hypotheses about what children predict, and also about how children should behave when they receive evidence that mismatches their predictions.…”
Section: Prediction and Processing In Young Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…This way we can differentiate between participants who are slowing down (those above the horizontal line) and those who are speeding up (those below the horizontal line) as they progress through the SRT trials. 7 Ramscar, Dye, and McCauley (2013) demonstrated that discrimination learning can have different consequences depending on the specific conditioning histories Ð i.e., earlier or later in learning, specific exposure can lead to diverging predictions and, consequently, behaviour. To control for this effect we randomized trials.…”
Section: Appendix B Stimulus Selection Proceduresmentioning
confidence: 99%